Effects of Current and Enhanced Tobacco Corrective Messages on Smokers' Intention to Quit Smoking and Intention to Purchase Cigarettes. Issue 4 (2nd May 2019) - Lee, Stella J; Sanders-Jackson, Ashley; Tan, Andy S L
Abstract: Introduction: A federal court has ordered tobacco companies to issue corrective messages to address tobacco-related misperceptions. This study examined the effects of viewing current versus two enhanced versions of tobacco corrective messages on smokers' intention to quit smoking and intention to purchase cigarettes. Methods: US adult smokers ( N = 803) were randomly assigned to view (1) two current tobacco corrective messages (Current), (2) two corrective messages that include an industry deception statement (Industry Deception), or (3) two corrective messages with an industry deception statement and testimonials of people harmed by smoking (Industry Deception + Testimonial). Outcomes were pretest–posttest change in intentions to quit smoking and posttest intention to purchase cigarette measures. Results: Intention to quit smoking increased significantly after viewing the Current corrective messages versus baseline. In addition, viewing the Industry Deception + Testimonial messages increased intention to quit smoking compared with the Current corrective condition and the Industry Deception condition. Hispanic smokers had increased intention to quit smoking and decreased intention to purchase cigarettes to a greater degree than non-Hispanic smokers in response to Industry Deception + Testimonial messages. There was no significant difference in intention to purchase cigarettes across conditions. Conclusions: Enhancing the current corrective statements by including an industry deception statement and testimonials may strengthen effects and contribute to remedying the effects of tobacco misinformation. Implications: Previous research has found that draft or proposed versions of tobacco industry corrective messages are effective in correcting beliefs and knowledge. However, studies have not examined how the current court-ordered corrective messages could change intention to quit smoking and intention to purchase cigarettes nor whether enhanced messages could perform better. Study findings suggest that the current corrective messages can increase smokers' intention to quit smoking beyond their baseline intention. More importantly, enhancing corrective messages by including an industry deception statement and testimonial was found to be more effective than current corrective messages. Findings can inform future iterations of tobacco correctives and strategies to reverse the effects of tobacco misinformation.